Use of the c-terminal coding region of Ligb for the molecular diagnosis (Ligbct PCR) of bovine leptospirosis in serum - Saraullo, Vanina Rosa; Hamer, Micaela; Esteban, Micaela; Sanchez, Maria Cristina; Brihuega, Bibiana Felicitas; Martinez, Mara Leila (International Leptospirosis Society, 2024)
Poster